AN ANALYSIS OF CHEMISTRY HIGH SCHOOL END-OF-YEAR EXAMS ACCORDING TO BLOOM’S COGNITIVE COMPLEXITY - Salamah Agung; Amrina Alhumaira; Dedi Irwandi Yuskar; Tika Reformatika Fuadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
ANALISIS UJIAN AKHIR KIMIA BERDASARKAN KOMPLEKSITASKOGNITIF TAKSONOMI BLOOMAbstractSchool exams has been used by teachers to determine the success of students’ learning. This research is aimed to determine the extent of students learning through an analysis of end-of-year exam items based on Bloom’s cognitive complexity. The exam instruments are gathered from chemistry teachers of 5 public schools, consisting of in total 190 5-multiple-choice items. Qualitative approach and theory-driven content analysis method using Bloom’s revised taxonomy of cognitive complexity were employed in the research. The result of this research showed that the majority of items (82.7%) determined students learning lower order cognitive skills (remember, understand, and apply). Skill of the analysis is the only higher order cognitive skill that has been found in the exam questions (17.3%). With regards to knowledge dimension, it was found that conceptual knowledge weighed the most among other dimensions (54.7%). It is interesting to see, however, that, the highest procedural knowledge was seen in the application skills (27.9%). This research suggests that chemistry teachers need to carefully determine exam questions according to the cognitive complexity in order to ensure the extent of students learning. For curriculum developer, this research can be used to consider the depth of students’ learning outcomes as they serve as the foundation for exam development. Further research can be done to determine the gap between the exams and the expected learning outcomes. This will be beneficial to understand the extent to which schools can go higher than the minimun learning outcomes determined by the government.AbstrakUjian sekolah telah digunakan oleh guru untuk menentukan keberhasilan belajar siswa. Penelitian ini bertujuan untuk mengetahui sejauh mana siswa belajar kimia melalui analisis materi ujian akhir sekolah berdasarkan kompleksitas kognitif Bloom. Instrumen ujian dikumpulkan dari 5 sekolah umum, yang terdiri dari 190 item soal pilihan ganda. Pendekatan kualitatif dan metode analisis isi yang digerakkan oleh teori menggunakan taksonomi kompleksitas kognitif Bloom yang telah direvisi digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa sebagian besar soal (82,7%) merupakan soal-soal dengan tingkat kognitif rendah (mengingat, memahami, dan menerapkan). Keterampilan analisis adalah satu-satunya keterampilan kognitif tingkat tinggi yang ditemukan dalam soal-soal ujian (17,3%). Untuk dimensi pengetahuan, ditemukan bahwa pengetahuan konseptual paling banyak di antara dimensi lainnya (54,7%). Menarik untuk dilihat, bagaimanapun, bahwa pengetahuan prosedural tertinggi terlihat pada keterampilan aplikasi (27,9%). Penelitian ini menyarankan guru untuk mempertimbangkan kompleksitas kognitif untuk memastikan sejauh mana siswa belajar.